Effect of vacuum and shrink packaging on shelf life of banana (Musa paradisica) - CLAUDIA K. L SUNISHA K; Er. George Mathew (Guide) (Tavanur 2015 DEPARTMENT OF FOOD AND AGRICULTURAL PROCESS ENGINEERING)
banana fruits are highly perishable and harvested banana crop ripen within 4-5 days after harvest under the ambient conditions in Kerala.
Effect of vacuum and shrink packaging on shelf life of banana (Musa paradisica)